Integrated neurovascular coupling (NVC) model: an fNIRS study on migraine - Taşdöğen, Selin. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Functional imaging techniques play a major role in monitoring the changes in brain hemodynamics. Migraine is one of the weirdest illnesses that have ever been described. It does not leave any symptom in patients like the other illnesses do, e.g. cancer. The most common symptom observed in migraine patients by the imaging techniques is the change in the brain hemodynamics. The existing mathematical model, Balloon Model, is described only for the hemodynamic changes in the venous compartment of the blood vessels in brain and it is thus not enough to describe the whole hemodynamic changes. The goal of this study was to improve the previous studies describing the venous compartment of the brain blood vessels by adding the arterial compartment hemodynamic changes as well as by integrating the CO2 kinetics into these models. The partial pressure of CO2 is the main parameter influencing cerebral blood flow, CBF, and was used as the input function since it is the driving force in the brain hemodynamics. Because the arterial compartment is rich in HbO2, the oxygen kinetics was also modeled and integrated to Balloon model. The present integrated modeling of brain hemodynamics enables us to understand the facts underlying the migraine illness and its pathophysiology clearly.
Keywords: Migraine.; Near infrared spectroscopy.